Neuronal mitochondrial morphology is significantly affected by both fixative and oxygen level during perfusion - Kim, Su Yeon; Strucinska, Klaudia; Osei, Bertha; Han, Kihoon; Kwon, Seok-Kyu; Lewis, Tommy L. (Frontiers in Molecular Neuroscience, 2022)
Neurons in the brain have a uniquely polarized structure consisting of multiple dendrites and a single axon generated from a cell body. Interestingly, intracellular mitochondria also show strikingly polarized morphologies along the dendrites and axons: in cortical pyramidal neurons (PNs), dendritic mitochondria have a long and tubular shape, while axonal mitochondria are small and circular. Mitochondria play important roles in each compartment of the neuron by generating adenosine triphosphate (ATP) and buffering calcium, thereby affecting synaptic transmission and neuronal development. In addition, mitochondrial shape, and thereby function, is dynamically altered by environmental stressors such as oxidative stress or in various neurodegenerative diseases including Alzheimer’s disease and Parkinson’s disease. Although the importance of altered mitochondrial shape has been claimed by multiple studies, methods for studying this stress-sensitive organelle have not been standardized. Here we address pertinent steps that influence mitochondrial morphology during experimental processes. We demonstrate that fixative solutions containing only paraformaldehyde (PFA), or that introduce hypoxic conditions during the procedure, induce dramatic fragmentation of mitochondria both in vitro and in vivo. This disruption was not observed following the use of glutaraldehyde (GA) addition or oxygen supplementation, respectively. Finally, using pre-formed fibril α-synuclein treated neurons, we show fixative choice can alter experimental outcomes. Specifically, α-synuclein-induced mitochondrial remodeling could not be observed with PFA only fixation as fixation itself caused mitochondrial fragmentation. Our study provides optimized methods for examining mitochondrial morphology in neurons and demonstrates that fixation conditions are critical when investigating the underlying cellular mechanisms involving mitochondria in physiological and neurodegenerative disease models.